2021
DOI: 10.1038/s41598-021-93430-2
|View full text |Cite
|
Sign up to set email alerts
|

The UL16 protein of HSV-1 promotes the metabolism of cell mitochondria by binding to ANT2 protein

Abstract: Long-term studies have shown that virus infection affects the energy metabolism of host cells, which mainly affects the function of mitochondria and leads to the hydrolysis of ATP in host cells, but it is not clear how virus infection participates in mitochondrial energy metabolism in host cells. In our study, HUVEC cells were infected with HSV-1, and the differentially expressed genes were obtained by microarray analysis and data analysis. The viral gene encoding protein UL16 was identified to interact with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…On one hand, it seems that many ULs protein-like virus domains are targets to mitochondria and interact with mitochondrial proteins. For example, UL12.5 proteins degrade mitochondrial DNA [ 15 ], and UL7 and UL16 also target mitochondria [ 14 , 26 , 27 ]. On the other hand, US3 and UL13 encode protein kinases that participate in the process of protein phosphorylation [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, it seems that many ULs protein-like virus domains are targets to mitochondria and interact with mitochondrial proteins. For example, UL12.5 proteins degrade mitochondrial DNA [ 15 ], and UL7 and UL16 also target mitochondria [ 14 , 26 , 27 ]. On the other hand, US3 and UL13 encode protein kinases that participate in the process of protein phosphorylation [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARL2 (GTP)-BART complex binds to the adenine nucleotide transporter (ANT), and ANT1 is the main chaperone of ARL2 (GTP)-BART complex 35,36 . The latest research reports that HSV-1 protein combines with ANT to promote the energy metabolism of mitochondrial cells 37 . ANT protein is a rich and indispensable component of the inner mitochondrial membrane, where it homodimerizes and forms a channel for the exchange of ATP and ADP, thereby controlling the ATP level in the cytoplasm 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Human Umbilical Vein Endothelial (HUVEC) cells was preserved and cultured in our laboratory 19 , maintained in Dulbecco's modi ed Eagle medium (Invitrogen, Carlsbad, CA) containing 10% FCS and supplemented with 100 units/ml penicillin and 100 μg/ml streptomycin in 0.3% collagen-coated dishes.…”
Section: Cells Viruses and Antibodiesmentioning
confidence: 99%
“…Adenine nucleotide translocator 2 (ANT2) is the most important signal transduction protein in the mitochondrial membrane and plays a crucial role in glycolysis metabolism. HSV‐1 UL16 interacts with ANT2 and significantly expands the content of intracellular ATP 115 …”
Section: Herpersviridaementioning
confidence: 99%
“…HSV-1 UL16 interacts with ANT2 and significantly expands the content of intracellular ATP. 115 Vastag et al 114 found that HSV-1 improves TCA cycle efflux toward producing pyrimidine nucleotide components. HSV-1 upregulates pyrimidine nucleotide biosynthesis by increasing aspartate generation, through elevated pyruvate carboxylase, glutamicoxaloacetic acid transaminase 2 (GOT2), and decreased AS1.…”
Section: Herpes Simplex Virus 1 (Hsv-1)mentioning
confidence: 99%